Metabolic intervention restores fertility and sperm health in non-obese diabetic rats - Tumentemur, Gamze; Titiz, Mustafa; Ors, Alev Bobus (Frontiers in Endocrinology, 2025)
BackgroundIn people with diabetes, the effect of sleeve gastrectomy on impaired sperm parameters, hormonal profile, and testis tissue remains controversial to some extent.The context and purpose of the studyThis study aimed to investigate the effects of sleeve gastrectomy on the hormonal profile, sperm parameters, and testis tissue in infertile rats with type II diabetes mellitus (TIIDM). This study included 32 rats with TIIDM with or without sleeve gastrectomy. All the rats underwent sperm, testis tissue, and serum hormone profile analyses before and 8 weeks after surgery.ResultsThere was a significant correlation between weight loss after sleeve gastrectomy and a decrease in glucose profile (p < 0.05). In the hormonal profile, testosterone improved significantly after 8 weeks following sleeve gastrectomy. There was a significant increase in sperm count (p < 0.05) and improved sperm morphology during the follow-up after sleeve gastrectomy. The analysis also showed significant changes in testis tissue after surgery.ConclusionSleeve gastrectomy significantly improved testosterone deficiency, testis tissue, and sperm count in rats with TIIDM. Further prospective clinical studies are needed to show how bariatric surgery affects infertility in patients with TIIDM.